2015
DOI: 10.1007/s00268-015-3231-1
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Impact of Anatomical Liver Resection for Hepatocellular Carcinoma with Pathologically Proven Portal Vein Invasion

Abstract: ALR confers a survival benefit for HCC patients with pPVI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
22
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 46 publications
1
22
0
Order By: Relevance
“…Patients with a pathologic finding of microscopic remnant tumor ( n = 20) or major vascular invasion ( n = 57) were excluded from the present analyses because these factors increase the risk of recurrence in resected HCC [9, 10]. Finally, 419 patients were included in the present study (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Patients with a pathologic finding of microscopic remnant tumor ( n = 20) or major vascular invasion ( n = 57) were excluded from the present analyses because these factors increase the risk of recurrence in resected HCC [9, 10]. Finally, 419 patients were included in the present study (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Resection methods and extent of liver resection should be planned individually after full consideration of tumour burden and liver function, aiming to achieve curative resection as well as to preserve future liver remnant as much as possible in patients with intermediate or advanced HCC and underlying cirrhosis. For patients with ipsilateral satellite nodules or macroscopic PVTT, AR is preferable and more likely to achieve an R0 resection in those with good liver function reserves. However, the survival data in the matched cohort indicated that, for diverse tumour burdens, the outcomes of AR and NAR were equivalent for patients with similar tumour burdens.…”
Section: Discussionmentioning
confidence: 93%
“…Because the indication for anatomical resection at our department is based on the ICGR15, decreased liver function would have been associated with the lower proportion of anatomical resection procedures in the high GAR group. Anatomical resection is closely related to HCC recurrence and prognosis after surgery, because both HCC progression and invasion extend along the portal vein . Therefore, the low rate of anatomical resection would have been associated with poor prognosis after potentially curative LR in the high GAR group.…”
Section: Discussionmentioning
confidence: 99%
“…,23 decreased liver function would have been associated with the lower proportion of anatomical resection procedures in the high GAR group. Anatomical resection is closely related to HCC recurrence and prognosis after surgery, because both HCC progression and invasion extend along the portal vein 40. Therefore, the low rate of anatomical resection would have been associated with poor prognosis after potentially curative LR in the high GAR group.With regard to operative characteristics, high GAR group had significantly higher operative blood loss and higher rate of red blood transfusion than those of low GAR group.…”
mentioning
confidence: 99%